POTRET PENDIDIKAN ISLAM: Perspektif Pembaruan Pemikiran dan Gerakan Islam Indonesia Kontemporer - Muljono Damopolii (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2007)
Snapshot of Islamic Education in this country can be explained through the historical reality, starting from developmental era to reformation era nowadays. Therefore, Islamic transformation whether thought aspect or movement, which can be understood clearly through explanation about: the first, innovation science epistemology, which emphasizes on religion science and general science have the same embryo is the unity of God. The second, the modern institution especially high education level relating with real institution condition that Islamic education is subordinate. The third, educational contem- porary issues that including Islamic education generally.